LaMnO3 nanoparticles supported on N doped porous carbon as efficient photocatalyst. (January 2019) - Hu, Jie; Zhang, Liang; Lu, Benqian; Wang, Xueqian; Huang, Hao
Abstract: A new type of photocatalyst by the dispersion of LaMnO3 nanoparticles on N doped porous biocarbon using a simple sol-gel method without adding any nitrogen source (such as NH3, NH4OH, N2 H4 ). Biochar is obtained from soybean dregs through two methods of hydrolysis and pyrolysis. The results show that the biocar obtained by two-step pyrolysis method is a better choice. The samples are characterized by field-emission scanning electron microscopy (FE-SEM), Raman spectroscopy, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), photoluminescence analysis, Brunauer-Emmett-Teller surface area analysis (BET) and UV-vis diffuse spectroscopy. It clearly demonstrates that composite exhibit an excellent photocatalytic activity in the degradation of Direct Green BE under UV-vis light because of its larger specific surface area, more active sites, improved charge separation efficiency and enhanced visible harvest ability. Furthermore, three typical N-bonding configurations in porous carbon is efficient for the enhanced photocatalytic activity, the h + and O2 − play main roles in the photocatalytic system. Graphical abstract: The mechanism that occurs in the LaMnO3 /N doped porous carbon during photocatalytic process is shown in the figure. N substitution at "regular" C sites and can be present of three typical N-bonding configurations such as pyridinic, pyrrolic or graphitic nitrogen. The graphitic N can act as the electron-transfer mediator for the photogenerated electrons. Moreover, the pyridinic N and pyrrolic N at the edges or defects can function as the activation region for the oxygen reduction. Highlights: Soybean dregs were used to prepare nitrogen doped porous carbon without adding any additional nitrogen sources. LaMnO3 nanoparticles anchored on N doped porous carbon as efficient photo-catalyst is the first application. The mechanism for the enhanced photocatalytic performance of composites was discussed.